Pengaruh Perkembangan Financial Technology terhadap Kepuasan Kualitas Pelayanan Transaksi - Hanum Auliya Rahmadhani; Ina Wadiatul Aqidah; Rizky Nur Yasin (VISA: Journal of Vision and Ideas, 2024)
The purpose of this study was to determine how the development of financial technology affects the satisfaction of transaction service quality. This research uses quantitative methods, and primary data is used in this research. This study used a non-probability purposive sample, with 108 respondents as the sample. In this study, data was used for multiple linear regression analysis. The test tool used is version 23 of the SPSS program. The results of this study state that the development of financial technology has a positive effect on transaction service quality satisfaction.